2017
DOI: 10.1111/exd.13443
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine crosstalk between endothelial cells and melanocytes through clusterin to inhibit pigmentation

Abstract: Cutaneous vasculature systems play a role in regulating skin pigmentation. We analysed RNA sequencing data to identify novel antimelanogenic factors secreted from endothelial cells and found that one of the secreted factors, clusterin, is highly expressed by HDMECs.To investigate the paracrine effect of clusterin from HDMECs on the regulation of melanogenesis, HDMECs were infected with clusterin or sh-clusterin lentivirus and the HDMEC-derived conditioned media were used to treat normal human melanocytes. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Aged skin samples showed upregulated expression of clusterin (CLU), a chaperone that inhibits both accumulation of elastin in photoaged skin [ 58 ] and melanogenesis through MITF/tyrosinase downregulation [ 59 ]. These actions may be related to characteristic phenotypes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Aged skin samples showed upregulated expression of clusterin (CLU), a chaperone that inhibits both accumulation of elastin in photoaged skin [ 58 ] and melanogenesis through MITF/tyrosinase downregulation [ 59 ]. These actions may be related to characteristic phenotypes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the perilesional normal skin, the hyperpigmented skin has been found to exhibit an upregulated expression of vascular endothelial growth factor (VEGF), a major angiogenic factor in UV‐exposed skin (Kim et al., 2007). Endothelial cells produce both melanogenic factors, such as nitric oxide and ET‐1 (Regazzetti et al., 2015; Suschek et al., 2004) and anti‐melanogenic factors, such as TGFβ1 and clusterin (Jo et al., 2009; Kim, Lee, et al., 2018; Kim, Shibata, et al., 2018; Park et al., 2016). These secretory factors derived from endothelial cells probably play regulatory roles in skin pigmentation.…”
Section: Role Of Intercellular Crosstalk In Age‐associated Hyperpigmentationmentioning
confidence: 99%
“…Several recent studies have highlighted the paracrine crosstalk between endothelial cells and melanocytes 14 17 . A recent study reported the regulatory function of melanocytes in vascularization, wherein choroidal melanocytes regulated uveal vascularization through the secretion of fibromodulin 16 .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a regulatory function of endothelial cells on melanocytes was discovered. Under physiological conditions, endothelial cells increase pigmentation by releasing endothelin-1 or inhibit pigmentation via transferrin growth factor (TGF)-β or clusterin 14 , 15 , 17 . However, how UV irradiation produces changes in endothelial cell secretions in relation to epidermal pigmentation is questionable.…”
Section: Introductionmentioning
confidence: 99%